Parliaments as Condorcet Juries: Quasi-Experimental Evidence on the Representation of Majority Preferences - David Stadelmann; Reiner Eichenberger; Marco Portmann (Center for Research in Economics, Management and the Arts (CREMA), 2011)
In parliament, individual representatives vote with a certain probability according to their constituents' preferences. Thus, the mechanism of the Condorcet Jury Theorem can be fruitfully applied to parliamentary representation: The probability that a majority of representatives votes according to the preferences of the majority of their constituents increases with the number of representatives per district. The political economy literature has so far disregarded this aspect. We provide a theoretical discussion and quasi-experimental evidence for the validity of the Condorcet Jury Theorem in parliamentary representation by contrasting unique data from parliamentary roll call votes and popular referenda decisions.
Keywords: D78; D70; D80; 330; Condorcet Jury Theorem; Preference Aggregation; Voting Behavior; Legislature; Political Representation